Quality Of Service During The Covid-19 Pandemic At Puskesmas, Karang Jaya District North Musirawas - Amalik, Davika; Imanda, Antonio; Saputra, Harius Eko (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
This study intends to determine the quality of service during the Covid-19 pandemic at the Karang Jaya District Health Center, North Musirawas Regency. This study uses a qualitative descriptive research method. The technique used is Accident Cluster Sampling, data collection techniques in this study are Observation, Interview, and Documentation According to Zeithaml et al (1990:63) there are seven dimensions of Service Quality: Tangible (Intangible), Medical equipment in the puskesmas is very lacking To carry out examinations and treatment of patients' illnesses, X-rays and ravid tests are not available, but they are limited in nature, there is only a laboratory for checking blood and patient diseases. So that people are disappointed with the limited facilities at the puskesmas. Reliability (Reliability) Treatments carried out by doctors and nurses are good because they have gone through a careful process starting with measuring body temperature, checking blood pressure and recording patient complaints before being examined by doctors. nurses in the treatment and examination of patients. The nurse in the treatment room and the examination is cool alone nagging with fellow friends so that the patient seems to be ignored, Assurance (Guarantee) Services and treatment carried out by nurses and doctors are not on time in providing services even though the service schedule and examination of patients' illnesses starts at 08 s /d 11:30 pm and Empaty . The services provided by the administration and doctors are very good with a friendly, polite and courteous attitude to greet patients when they pass in front of the patient. Meanwhile, nurses are less friendly and polite in front of patients, nurses do not greet patients in the waiting room at all.